A role of FCER1A and FCER2 polymorphisms in IgE regulation. Issue 2 (20th December 2013) - Sharma, V.; Michel, S.; Gaertner, V.; Franke, A.; Vogelberg, C.; von, A.; Bufe, A.; Heinzmann, A.; Laub, O.; Rietschel, E.; Simma, B.; Frischer, T.; et al.
Abstract Background Both FCER2 and FCER1A encode subunits of IgE receptors. Variants in FCER1A were previously identified as major determinants of IgE levels in genome‐wide association studies. Methods Here we investigated in detail whether FCER2 polymorphisms affect IgE levels alone and/or by interaction with FCER1A polymorphisms. To cover the genetic information of FCER2, 21 single‐nucleotide polymorphisms (SNPs) were genotyped by Illumina HumanHap300 BeadChip (5 SNPs) and the matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS; 14 SNPs) in at least 1303 Caucasian children (651 asthmatics) (ISAAC II/ MAGICS population); genotypes of two SNPs were imputed. Results SNP rs3760687 showed the most consistent effect on total serum IgE levels (b [SE] = −0.38 [0.16]; P = 0.016), while FCER2 polymorphisms in general were predominantly associated with mildly‐to‐moderately increased IgE levels (50th and 66th percentiles). Gene‐by‐gene interaction analysis suggests that FCER2 polymorphism rs3760687 influences IgE levels mainly in individuals not homozygous for the risk allele of FCER1A polymorphism rs2427837, which belongs to the major IgE‐determining tagging bin in the population. Conclusion FCER2 polymorphism rs3760687 affects moderately elevated total serum IgE levels, especially in the absence of homozygosity for the risk allele of FCER1A SNP rs2427837.